2005
DOI: 10.1103/physrevlett.94.085901
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer between Two Nanoparticles Through Near Field Interaction

Abstract: We introduce a thermal conductance by using the fluctuation-dissipation theorem to analyze the heat transfer between two nanoparticles separated by a submicron distance. Using either a molecular dynamics technique or a model based on the Coulomb interaction between fluctuating dipoles, we derive the thermal conductance. Both models agree for distances larger than a few diameters. For separation distances smaller than the particle diameter, we find a transition regime characterized by a thermal conductance larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
199
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(216 citation statements)
references
References 20 publications
13
199
3
1
Order By: Relevance
“…For sufficiently large distances, heat exchange proceeds via thermal radiation, through emission or absorption of photons, whereas at smaller distances, recent molecular dynamics simulations have shown that the Coulomb interaction ͑near-field radiation͒ is the dominant mechanism. 7 For near-field interactions, the thermal conductance was calculated under the assumption that both NPs behave as effective dipoles at different temperatures. 7 Hence, since these dipoles undergo thermal fluctuations, the fluctuationdissipation theorem ͑FDT͒ [8][9][10][11] provides the energy which dissipates into heat in each NP.…”
Section: Introductionmentioning
confidence: 99%
“…For sufficiently large distances, heat exchange proceeds via thermal radiation, through emission or absorption of photons, whereas at smaller distances, recent molecular dynamics simulations have shown that the Coulomb interaction ͑near-field radiation͒ is the dominant mechanism. 7 For near-field interactions, the thermal conductance was calculated under the assumption that both NPs behave as effective dipoles at different temperatures. 7 Hence, since these dipoles undergo thermal fluctuations, the fluctuationdissipation theorem ͑FDT͒ [8][9][10][11] provides the energy which dissipates into heat in each NP.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very recent experiments [6,7] were in good quantitative agreement with theoretical predictions. On the theoretical side, we can highlight the studies of the heat flux for layered media [8,9], for photonic crystals [10], metamaterials [11], and porous media [12].In addition, the dependence of the heat transfer on the geometry has attracted much interest and has been investigated in a sphere-plane geometry [13,14], for spheroidal particles above a plane surface [15] and between two spheres or nanoparticles [16][17][18][19][20]. Somewhat more applied studies have attempted to take advantage of the potential of the tremendous increase of the radiative heat flux on the nanoscale for thermal imaging of nanostructured surfaces [21][22][23][24].…”
mentioning
confidence: 99%
“…In addition, the dependence of the heat transfer on the geometry has attracted much interest and has been investigated in a sphere-plane geometry [13,14], for spheroidal particles above a plane surface [15] and between two spheres or nanoparticles [16][17][18][19][20]. Somewhat more applied studies have attempted to take advantage of the potential of the tremendous increase of the radiative heat flux on the nanoscale for thermal imaging of nanostructured surfaces [21][22][23][24].…”
mentioning
confidence: 99%
“…The enhancement of HT in the near-field regime (generally denoting separations small compared to the thermal wavelength, which is roughly 8 microns at room temperature) has only recently been verified experimentally [5,6]. Theoretically, HT has been considered for a limited number of shapes: Parallel plates [2,3,7,8], a dipole or sphere in front a plate [9][10][11], two dipoles or spheres [9,12,13], and for a cone and a plate [14]. The scattering formalism has been successfully exploited [10,[15][16][17][18] in this context.…”
mentioning
confidence: 99%